2019
DOI: 10.1063/1674-0068/cjcp1902032
|View full text |Cite
|
Sign up to set email alerts
|

Infrared photodissociation spectroscopic and theoretical study of [Co(CO2)n]+ clusters

Abstract: The mass-selected infrared photodissociation (IRPD) spectroscopy was utilized to investigate the interactions of cationic cobalt with carbon dioxide molecules. Quantum chemical calculations were performed on the [Co(CO 2) n ] + clusters to identify the structures of the low-lying isomers and to assign the observed spectral features. All the [Co(CO 2) n ] + (n=2−6) clusters studied here show resonances near the CO 2 asymmetric stretch of free CO 2 molecule. Experimental and calculated results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In contrast, the CO 2 molecule was only weakly bound to the metal cations, exclusively in an end-on configuration via electrostatic charge-quadrupole interaction, resulting in a linear M + OCO structure. The antisymmetric CO 2 stretching vibrations in these cationic complexes are generally blue-shifted with respect to the free CO 2 molecule. It was found that these blue-shifted vibrations vary only slightly from one system to another due to electrostatic interaction. Here we report the generation of the cationic metal complex BeOCO + , which exhibits an antisymmetric CO 2 stretching mode at 2418.9 cm –1 in solid neon, blue-shifted by 71 cm –1 with respect to free CO 2 . The observed value is the highest antisymmetric CO 2 stretching frequency ever reported for a carbon dioxide complex. …”
Section: Introductionmentioning
confidence: 83%
“…In contrast, the CO 2 molecule was only weakly bound to the metal cations, exclusively in an end-on configuration via electrostatic charge-quadrupole interaction, resulting in a linear M + OCO structure. The antisymmetric CO 2 stretching vibrations in these cationic complexes are generally blue-shifted with respect to the free CO 2 molecule. It was found that these blue-shifted vibrations vary only slightly from one system to another due to electrostatic interaction. Here we report the generation of the cationic metal complex BeOCO + , which exhibits an antisymmetric CO 2 stretching mode at 2418.9 cm –1 in solid neon, blue-shifted by 71 cm –1 with respect to free CO 2 . The observed value is the highest antisymmetric CO 2 stretching frequency ever reported for a carbon dioxide complex. …”
Section: Introductionmentioning
confidence: 83%
“…Transformation of carbon dioxide into valued chemicals has received increasing attention in the past few decades. , The coordination and activation of carbon dioxide by transition metal centers are considered as key steps in the catalytic transformation of the extremely thermodynamically stable carbon dioxide into useful organic substances. The interactions of metal atoms and ions with carbon dioxide may serve as a simple model for understanding the catalytic mechanism and have been intensively studied experimentally either in the gas phase or in solid noble gas matrices. Spectroscopic studies indicate that carbon dioxide forms various complexes with transition metals in different coordination modes, including η 1 -O end-on, η 1 -C, η 2 -C, O, and η 2 -O, O (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 ligand is bound to the metal center exclusively in an end-on η 1 -O fashion in the cationic complexes. 21–35 The binding between the metal cation and carbon dioxide is largely an electrostatic interaction, resulting in a blue-shifted antisymmetric CO 2 stretching vibration with respect to the free CO 2 molecule. 21–35 Solvation-induced metal cation → carbon dioxide electron transfer with the formation of a bent CO 2 − moiety was reported on the Mg(H 2 O) n (CO 2 ) + complexes with n ≥ 3.…”
Section: Introductionmentioning
confidence: 99%
“…21–35 The binding between the metal cation and carbon dioxide is largely an electrostatic interaction, resulting in a blue-shifted antisymmetric CO 2 stretching vibration with respect to the free CO 2 molecule. 21–35 Solvation-induced metal cation → carbon dioxide electron transfer with the formation of a bent CO 2 − moiety was reported on the Mg(H 2 O) n (CO 2 ) + complexes with n ≥ 3. 27 Metal cation → ligand electron transfer reaction in forming an oxalate-type C 2 O 4 anion species was proposed in the V(CO 2 ) n + n ≥ 7 clusters, 28 which was later reassigned to a charge transfer complex involving a bidentate η 2 -C, O coordinated CO 2 − ligand.…”
Section: Introductionmentioning
confidence: 99%